Contemporary architecture as cultural value. Vilnius case - Nekrošius, Liutauras (Journal of Architecture and Urbanism, 2012)
Within the whole town scale, the heritage objects of Vilnius contemporary architecture represent a relatively small (40 out of more then 2,500), but rather significant – due to their typological composition (most important public objects and districts of the city) and geographical location (centers and sub-centers) – group of buildings highly influencing the image of the capital city. The group encompasses the town-planning objects (two residential districts, students’ campus in Saulėtekis Ave, the New Town Center and complex of the Parliament buildings), architecture objects (15 public use buildings, 3 public interiors and 6 apartment houses), as well as historical objects (1 bridge, 1 public use and 1 residential buildings).The group of protected heritage objects was mostly developed during the occupation period, in the 1980-ies, according to the legislation of the time, prevalent political and artistic trends, as well as conditions of the planned economy and state (public) ownership. Following the essential transformations in the socio-cultural context, this group has been failed to reevaluate in a systemic way, without any new structure and conservation concept being formed in compliance with the new conditions. This has inflicted some damage to expression of the public image of the city and understanding of its values, needless to say that highly valuable buildings have been just left to fade away. Considering that it is highly relevant to maintain the most valuable architectural objects of the second half of the 20th century for future generations, it is essential to perform a physical status and use monitoring of heritage objects of contemporary architecture, update the data of heritage stocktaking, identify the boundaries of authorship rights (copyright) and real estate cultural heritage protection, estimate values of the protected objects, reconsider the ways of management and coordinate the processes of document revision and building renovation/ transformation.Article in Lithuanian.Sovietinių metų architektūra kaip kultūros vertybė Vilniaus atvejisSantrauka. Šiandieninėje Lietuvoje vykstantis sovietinių metų modernizmo architektūros paveldo objektų apsaugos procesas ir taikomos priemonės straipsnyje nagrinėjami remiantis Vilniaus miesto pavyzdžiu. Analizuojami po 1961 m., t. y. formalaus amžiaus cenzo neatitinkantys, Vilniuje įgyvendinti architektūrinio ir urbanistinio vertingųjų savybių pobūdžio nekilnojamojo kultūros paveldo objektai ir vietovės. Tokių kūrinių Kultūros vertybių registre įvairiais skaičiavimais yra apie 40. Ši grupė XX a. II-ojoje pusėje formuota kaip raiškiai atspindinti laikotarpio architektūrinės kūrybos tendencijas bei tuometes politines nuostatas, tačiau po 1990 m. iš esmės nerevizuota, šiandien dėl pakitusių sociokultūrinių ir ekonominių sąlygų praranda turėtą artikuliaciją. Tai lėmė ir skirtingą objektų fizinę būklę.Straipsnyje siekiama atskleisti aktualiausias problemas, susijusias su kūrinių saugojimu, su įvykusiais objektų ir vietovių pakitimais. Svarstomos galimos tolesnės saugojimo kryptys, būdai. Bandoma formuluoti svarbius konceptualiuosius ir vertybinius klausimus, autoriaus manymu, būtinus kelti platesnių profesinių ir mokslinių diskusijų lygmeniu.Reikšminiai žodžiai: kultūros paveldas, kultūros vertybių registras, paveldo politika, Vilniaus modernizmo architektūra, sovietinė architektūra.